Health-Related Quality of Life among Iranian Women with Uterine Fibroids: A Cross Sectional Study - Hanieh Najafiarab; Farah Farzaneh; Niki Talebian; Zahra Ghasemi; Maryam Talayeh (Tehran University of Medical Sciences, 2024)
Objective: Uterine fibroids (UFs) are the most common benign tumors in women, and their prevalence varies between 5.4 and 77.0% in reproductive-aged women. Patients with UFs may experience severe symptoms that they can affect different aspects of their lives, including quality of life. This study aimed to investigate the health-related quality of life among Iranian women with UFs. Materials and methods: This cross-sectional study was conducted at Imam Hossein Hospital, Tehran, Iran, between November 2023 and February 2024, Data collection was based on the census method. Uterine Fibroid Symptom and Health-related Quality of Life (UFS-QOL) questionnaire was used to assess symptom severity and health-related quality of life (HRQOL) of women with UFs. Data were analyzed using the SPSS software version 23.0. Results: Overall, 220 patients with a mean age of 43.10±5.01 years were included in the study. Patients had total UFS-QOL score of 64.11±20.35 with the following subscales' scores: symptom severity: (19.00±6.39), concern: (60.79±26.47), activities: (71.76±23.02), energy/mood: (54.39±25.14), control: (66.52±22.82), self-consciousness: (77.63±26.39), and sexual function: (59.40±31.18). Furthermore, patients with multiparity history (P= 0.001), obesity (P<0.001), increased menstrual duration (P<0.001), irregular menstruation (P<0.001), and hyper menorrhea (P<0.001) had lower HRQOL scores. Conclusion: All subscales' scores of HRQOL were over 50 in patients with UF. HRQOL in these patients can be affected by certain factors, such as features of the menstrual cycle, multiparity, and obesity.